Exploring English Language Needs for Tour Guides in Heritage Tourism : A Case Study at Mangkunegaran Palace in Indonesia - Avantie, Chevia Altika; Kurniawati, Diaz; Nabila, Shelvia Ariesta; Suharyanto, S; Ariatmi, Siti Zuhriah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to examine the English language requirements of tour guides at Mangkunegaran Palace to support the preparation of tourism students in meeting the practical demands of the guiding profession. English proficiency is essential in traditional tourism contexts such as Mangkunegaran Palace, which receives a considerable number of foreign visitors. Methodology: An exploratory qualitative approach was employed to investigate the English needs of professional tour guides. Data were collected through interviews with five selected tour guides based on their experience and length of service. The interviews focused on the English tasks they perform and the specific language demands of their roles. Results: The findings indicate that most tour guides have an educational background in tourism or a related field. They frequently utilize their speaking and listening skills when guiding tourists, and the English training they received in school has been beneficial. A notable challenge they face is understanding the diverse accents of international tourists, which can hinder effective communication. Applications/Originality/Value: The study suggests that well-designed English for Specific Purposes (ESP) courses are essential to support tour guide professionals. These courses should emphasize the development of practical communication skills tailored to real-world tourism contexts, particularly in handling cross-cultural and multilingual interactions.